Unpacking Peer Collaborative Experiences in Pre-Class Learning of Flipped Classroom With a Production-Oriented Approach - Shu-Rong Zhao (SAGE Publishing, 2021)
In flipped learning (FL), the pre-class section plays an important role and determines whether meaningful and deep-level learning can take place in the following in-class section. However, previous studies focus on in-class learning and research little on the pre-class section. In order to explore an interactive mode which can ensure the effect of pre-class learning, a production-oriented peer collaboration FL framework was proposed and applied to the Business English course. Mixed research methods including questionnaire and focus group interview were used to test the effectiveness of the framework and explore effective forms of interaction. Data analysis shows that the FL framework improved significantly social interaction self-efficacy, help-seeking, and self-evaluation in self-regulated learning, thus ensured quality pre-class learning. As to interaction, eight collaboration forms were found through thematic analysis, namely comparison, correction, reaching agreement, supervision, inspiration, complementation, negotiation, and emotional support. Among them, comparison is the most beneficial and frequently mentioned collaborative behavior. This research provides an empirical case for peer interaction based on online learning tasks. It helps enrich interactive research in FL and provides teaching reference for practitioner teachers by offering a feasible framework.